2021
DOI: 10.1152/ajpregu.00032.2021
|View full text |Cite
|
Sign up to set email alerts
|

Transient effects of forebrain ischemia on fetal heart rate variability in fetal sheep

Abstract: Fetal heart rate variability (FHRV) is a key index of antenatal and intrapartum fetal well-being. FHRV is well established to be mediated by both arms of the autonomic nervous system, but it remains unknown whether higher centers in the forebrain contribute to FHRV. We tested the hypothesis that selective forebrain ischemia would impair the generation of FHRV. Sixteen chronically instrumented near-term fetal sheep were subjected to either forebrain ischemia induced by bilateral carotid occlusion or sham-ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…This is broadly consistent with evidence that even severe forebrain injury does not affect FHRV, supporting the hypothesis that the hindbrain is essentially the sole origin of HRV in the fetus 58 . Of particular interest, one study in preterm fetal sheep has shown that the brainstem was relatively spared from LPS-induced injury and inflammatory changes despite LPS triggering cerebellar injury 56 .…”
Section: Discussionsupporting
confidence: 86%
“…This is broadly consistent with evidence that even severe forebrain injury does not affect FHRV, supporting the hypothesis that the hindbrain is essentially the sole origin of HRV in the fetus 58 . Of particular interest, one study in preterm fetal sheep has shown that the brainstem was relatively spared from LPS-induced injury and inflammatory changes despite LPS triggering cerebellar injury 56 .…”
Section: Discussionsupporting
confidence: 86%
“…In the fetus at least, normal FHRV seems to be almost entirely mediated by the brainstem, with full recovery of FHRV after severe forebrain ischaemic injury in near‐term fetal sheep (Maeda et al . 2021).…”
Section: Preclinical Insights Into Intrapartum Fhrvmentioning
confidence: 99%
“…At a systemic level, the appearance of a normal FHR and FHRV amplitude and pattern including regular sleep cycling, as shown by alternate periods of high and low absolute levels, is widely believed to represent an expression of a healthy, fully intact central nervous system (Ugwumadu, 2014). In the fetus at least, normal FHRV seems to be almost entirely mediated by the brainstem, with full recovery of FHRV after severe forebrain ischaemic injury in near-term fetal sheep (Maeda et al 2021).…”
Section: Preclinical Insights Into Intrapartum Fhrvmentioning
confidence: 99%